REVIEW ON VANET ARCHITECTURE AND APPLICATIONS (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Rapid advances in wireless technology have been occurring in recent years. Nowadays, most research is conductedin the field of telecommunication. In the area of wireless communication, VANET is the fastest growing area. Amobile ad hoc network (MANET) is defined as a network that operates ad hoc on a mobile device (VANET) andwhich can be used to improve the road safety and also to improve the experience of passengers. VANET iscomprised of vehicles to vehicles (V2V) and vehicles to infrastructure (V2I) communications supporting IEEE802.11p wireless access technologies. ITS (Intelligent Transport Systems) are expected to improve road safety andmotor traffic efficiency through this innovation in wireless communication. In order to make the VANET morerobust, many issues must be addressed. An infrastructure based VANET might use mobile vehicles as sensors. Bydetecting, gathering, and disseminating real-time data about traffic conditions and road hazards, they can be able todetect, gather and share traffic information. This paper focuses on the history of VANETs, their challenges andpotentials, as well as the way to preventing the long-awaited ITS.